The effect of booktrack on students reading comprehension ability - Lis Septia Ningsih; Hendra Sudarso (Penerbit STKIP PGRI Bangkalan, 2020)
The purpose of this study was to determine the effect of Booktrack on listening to students in reading comprehension skills. Booktrack is a free web application that synchronizes digital books with audio, producing a deep reading experience. The sample of this study was class VII of Junior high school AL KAHFI SEPULU as an experimental class and as a control class that consists of 20 students. The method in this study is a quantitative method. In addition, the design used was pre-experimental research, and the instrument was tests. This research was taken using non-random sampling. In addition, this research was carried out through the following procedures: giving pre-test, applying treatment and giving post-test. Data were analyzed and processed using ANCOVA statistical data calculations by the SPSS 23 program. Significant shown by the average post-test of students in the experimental class was 50.00 and the post-test average in the control class was 48.00. The results of the statistical hypothesis test was 0.021 from the p-value. This was lower than the significant level of 0.05. If the p-value <of the significant level is 0.05. This means H1 is accepted and H0 is rejected. In conclusion, this Booktrack media is effective as a teaching medium to improve reading comprehension in grade VII students at Junior high school al Kahfi Sepulu.